Moral Values in Digital Learning: Applying Thomas Lickona’s Framework in Online Higher Education - Prabowo, Cahyaningtias Dwi (Journal of Islamic Education Management Research, 2024)
Purpose – This study investigates the integration of Thomas Lickona’s moral values of respect and responsibility into online character education at Siber Muhammadiyah Yogyakarta University, addressing the gap where digital learning prioritizes knowledge over attitudinal development. It evaluates how these values are embedded institutionally and pedagogically, offering insights into balancing cognitive and ethical growth in digital higher education. Design/methods – A qualitative case study was conducted during the 2024 even semester, employing interviews with lecturers and students, non-participant observations of online interactions, and analysis of syllabi, learning matrices, and institutional documents. Data were coded using Creswell’s six-phase model and triangulated across sources (participants, methods) to ensure validity. Findings – Responsibility was systematically integrated via structured curriculum design, task-based assessments (e.g., quizzes, UCPMK exams), and progress-tracking tools (e.g., LMS dashboards). However, respect remained implicit, lacking explicit learning outcomes or evaluative metrics. Collaborative stakeholder engagement and flexible learning systems reinforced responsibility, but respect relied on informal practices like motivational discussions, with no formal assessment. Research implications/limitations – The single-institution focus limits generalizability, and potential respondent bias (e.g., reliance on self-reported data) may affect findings. Qualitative methods prioritized depth over breadth, warranting future quantitative validation. Practical implications – The university’s responsibility-centric model offers a blueprint for online institutions to formalize moral education through academic planning and digital tools. To cultivate respect, recommendations include integrating peer collaboration projects, ethical scenario-based modules, and explicit respect-related competencies into syllabi. Stakeholder training on intergenerational value modeling could further enhance cultural alignment. Originality/value – This study uniquely applies Lickona’s framework to online higher education, revealing how digital environments can operationalize moral values through curriculum design. It bridges theoretical discourse on character education with practical strategies for hybrid learning contexts, offering actionable pathways to harmonize cognitive and ethical development in rapidly evolving educational landscapes.